STABILITY OF MODERN ARCHES - Khadzhieva S. S. (Modern American Journals, 2025)
In modern architecture, arches have historically been one of the most important elements of architecture, but their constructive and aesthetic significance remains relevant today. Through innovations and innovations, new forms and materials for arches are being developed. This article discusses the role of modern arches, their constructive features, functional purposes and aesthetic values.
Keywords: Modern arches, architecture, constructive features, aesthetics, innovation, materials, history of architecture.